Melhoria nas características sensoriais de pão isento de glúten a partir da fermentação natural - Tonetto, Tatiane Codem (2018)
Due to the increase in the diagnosis of celiac disease and other disorders caused by gluten, as well as people who follow an alternative diet, consumption and the search for gluten-free bread products have increased, especially for bread. However, gluten-free baking has been shown to be the main technological challenge, since in the absence of this protein, bread is characterized as unattractive to consumption, because of the very sensorial difference of traditional bread. Therefore, the objective of this study was to prepare gluten-free breads, using natural yeast produced from rice flour in search of improvements in technological, sensory and shelf life characteristics. The yeast was developed by the spontaneous fermentation of rice flour and had the physical-chemical parameters (pH and titratable acidity) and microbiological parameters (counting of lactic acid bacteria and molds and yeasts) monitored during its manufacture. Subsequently, breads were prepared with three different concentrations of natural yeast: 10, 20 and 30g for each 100g of starch source, which were compared with control treatment developed with commercial yeast. Analyzes of specific volume, water activity, moisture, texture and color of the crust and crumb and firmness were carried out in order to determine the technological quality of the breads. To follow the shelf life of the loaves, the counts of mold and yeast and aerobic mesophiles, water activity, moisture and analysis of the firmness of the crumb were performed on days 1, 3 and 5 after brewing. In addition, the microbiological safety of breads was guaranteed according to current legislation, by counting Coliformes at 45ºC, Salmonella sp and Bacillus cereus, to be sensorially evaluated by a panel of untrained tasters, through affective acceptance and purchase intention tests and affective of order of preference. The results showed differences (p <0.05) for volume and color between treatments developed with natural yeast and with commercial yeast, but which are visually imperceptible. There was an inhibition on fungal growth and a reduction in the rate of hardening of the kernel, these being proportional to the concentration of natural yeast used. This study evidences the natural yeast, developed with rice flour, as a tool capable of adding benefits to gluten-free breads, mainly regarding the increase in shelf life without the use of chemical additives.